PERANCANGAN SISTEM INFORMASI PERSEDIAAN STOK BARANG PADA GUDANG PT BANK NEGARA INDONESIA PERSERO (TBK) - Fredy, Julian; Harman, Rika (LPPM Universitas Putera Batam, 2021)
PT Bank Negara Indonesia is one of the oldest banks in the history of the republic of Indonesia which is a state-owned bank. This BNI bank was established on July 5, 1946 and currently BNI already has 1,076 offices throughout Indonesia and several branch offices that are established overseas. Banking has a goal, namely to assist in the development and improvement of economic growth in improving the welfare of the people, which is the oldest in the Act of 1998 Number 10. Based on this purpose, banking in Indonesia must fulfill obligations and fulfill functionalities based on the principles of the people's economy. From this objective, banks in Indonesia must carry out their duties and functions properly and based on economic democracy. The problem that often occurs is if there are too many requests for goods from various outlets, resulting in a large number of request papers being stored and will be reported to the superior as a transaction for the release of goods in the warehouse which results in loss of information and data, thus affecting the final report With the Inventory Inventory Information System Application, the admin can control the entry and exit of goods easily, quickly and efficiently.